Assessment of the requirement for aquaporins in the thylakoid membrane of plant chloroplasts to sustain photosynthetic water oxidation. Issue 14 (31st May 2013) - Beebo, Azeez; Mathai, John C.; Schoefs, Benoît; Spetea, Cornelia
Abstract : Oxygenic photosynthetic organisms use sunlight energy to oxidize water to molecular oxygen. This process is mediated by the photosystem II complex at the lumenal side of the thylakoid membrane. Most research efforts have been dedicated to understanding the mechanism behind the unique water oxidation reactions, whereas the delivery pathways for water molecules into the thylakoid lumen have not yet been studied. The most common mechanisms for water transport are simple diffusion and diffusion facilitated by specialized channel proteins named aquaporins. Calculations using published data for plant chloroplasts indicate that aquaporins are not necessary to sustain water supply into the thylakoid lumen at steady state photosynthetic rates. Yet, arguments for their presence in the plant thylakoid membrane and beneficial action are presented. Abstract : Significant water amounts are consumed daily for photosynthesis in chloroplasts. Simple diffusion may sustain water supply at steady state photosynthetic rates. Low Ea of water transport indicates the presence of aquaporins in thylakoids. Aquaporins could contribute to fast regulatory volume changes of the thylakoid lumen. Proteomic evidence of PIPs and TIPs in chloroplasts deserves further investigation.